Diversifying U.S. Crop Production - Janick, Jules; Blase, Melvin G.; Johnson, Duane L.; Jolliff, Gary D.; Myers, Robert L. (Council for Agricultural Science and Technology (CAST), 1996)
For more than a century, crop price instability has dogged U.S. farmers. And in the past 60 years–despite federal subsidy and acreage reduction programs meant to stabilize farm income–farm numbers, farm populations, and rural prosperity have declined ominously. Public concerns over food safety, commodity program costs, and agricultural sustainability have become important policy issues. Restriction of research funding and crop support payments to major commodity crops has undermined the potential of new crops to alleviate related concerns and pressures. The search for and development of new crops is critical to U.S. agriculture and would improve its sustainability through diversification.
Keywords: U.S. Crop Production; Crop Price Instability; Commodity Programs